Pelatihan Pembuatan Minuman Kesehatan Berbasis Kunyit pada Masyarakat Desa Tenaru, Gresik, Jawa Timur: Training on Making Turmeric-Based Health Drinks for the Tenaru Village Community, Gresik, East Java - Juni Ekowati; Arie Sulistyorini; Suzana Suzana; Andang Miatmoko; Kholis Amalia Nofianti; Farida Ifadotunnikmah; Diajeng Putri Paramita; Firmansyah Ardian Ramadhani; Dwi Setyawan; Noorma Rosita; Muh. Agus Syamsur Rijal; Ersanda Nurma Praditapuspa; Winanda Rizki Febrianti; Dita Savitri; Adam Pratama (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Turmeric is a herbal remedy with a million benefits that has been used by Indonesians for centuries. Tenaru Village, one of the villages, produces a lot of turmeric annually in Gresik Regency. However, this turmeric is sold only as a cash crop or a simple product at a low price. This program aims to provide training for Tenaru village farmers to create innovative turmeric-based products to increase their selling value. Furthermore, this program aims to increase participants' understanding of safe food packaging as part of safe, high-quality food products. The program's success was evaluated quantitatively, showing a statistically significant increase in pre- and post-test scores. The qualitative assessment using Bloom's taxonomy analysis showed an increase in participants' abilities, from not knowing to being able to teach other people in that village. This indicates that the program has had a significant impact on participants' ability to develop innovative turmeric-based instant beverage products.